2023
DOI: 10.1039/d3nj00862b
|View full text |Cite
|
Sign up to set email alerts
|

[DDQM][TFSI]: a room temperature ionic liquid as an active electrode material for supercapacitor devices and a catalyst for rapid synthesis of 4-aryl-NH-1,2,3-triazoles under microwave irradiation

Abstract: A multifunctional room temperature ionic liquid [DDQM][TFSI] has been designed and its properties have been investigated to be used as an electrolyte. The RTIL bears superior catalytic properties as well...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Dutta et al also reported a newer and green approach for obtaining 1,2,3-triazoles ( 57a–57j ), in which various benzaldehyde derivatives were reacted with nitromethane and sodium azide using1-dodecylquinolin-1-ium bis(trifluoromethane)sulfonimide ([DDQM][TFSI]) in dimethyl sulfoxide under microwave irradiation (Scheme 61). 138 All the triazoles were obtained in good to high yields (65%–94%) within 2 min. As shown in Scheme 62, the plausible mechanism involved the initial formation of nitrostyrene from the reaction of aldehyde derivatives with nitroalkanes, which, in addition to the azide to the CC bond, formed an intermediate (I).…”
Section: Green Synthesis Of 123-triazolesmentioning
confidence: 92%
“…Dutta et al also reported a newer and green approach for obtaining 1,2,3-triazoles ( 57a–57j ), in which various benzaldehyde derivatives were reacted with nitromethane and sodium azide using1-dodecylquinolin-1-ium bis(trifluoromethane)sulfonimide ([DDQM][TFSI]) in dimethyl sulfoxide under microwave irradiation (Scheme 61). 138 All the triazoles were obtained in good to high yields (65%–94%) within 2 min. As shown in Scheme 62, the plausible mechanism involved the initial formation of nitrostyrene from the reaction of aldehyde derivatives with nitroalkanes, which, in addition to the azide to the CC bond, formed an intermediate (I).…”
Section: Green Synthesis Of 123-triazolesmentioning
confidence: 92%